Carotenoid Analysis of Ripe Banana Flesh and Peel from Three Cultivars of Banana - Septiany, Gabriela Johana; Putri, Widya Dwi Rukmi; Panca, Ida Nur; Heriyanto, Heriyanto; Limantara, Leenawaty (Ma Chung Research Center for Photosynthetic Pigments, 2019)
Banana peel is a promising source to be utilized in fortification of food products due to the high content of carotenoids (Cars) which are active as provitamin A. Dominant, total and relative concentrations of Cars were determined from fresh flesh and peel in three cultivars of banana obtained from Raja, Ambon Kuning, and Kepok Kuning. To evaluate the difference in Car compositions principal component analysis (PCA) was also performed. Based on chromatographic, spectroscopic, and mass spectrometric analyses, dominant Cars were separated and identified to be lutein, Î±-carotene and Î²-carotene. Lutein was the major Car of fresh peel, while other two Cars were found in fresh flesh in addition to lutein. Raja banana had the highest total concentration of Cars among three banana samples used. PCA results generated from the absorption spectra showed three clusters of the different banana samples. PCA results are correlated to their Car compositions and this method might be applicable for the determination of dominant Cars.